(untitled) (Journal of Academic Finance, 2022)
Objective: Traditional finance emphasises market efficiency and inherent behavioural anomalies in investors. However, the emergence of the adaptive market hypothesis tends to suggest otherwise. The adaptive market hypothesis challenges market efficiency and behavioural finance by contesting that investors and market participants adapt to changing market environment. In essence, investors learn from their mistakes. The purpose of this study was to explore the concept of an adaptive market hypothesis in five international markets, namely, the JSE, CAC 40, NASDAQ, JPX-NIKKEI and DAX. Method: This study used a variance ratio test to explore the adaptive market hypothesis from January 2017 to April 2022. Results: the findings revealed the existence of adaptive markets in the CAC 40 and NASDAQ during the period under review. Conversely, there was no statistical evidence to support the adaptive concept in the JSE, JPX-NIKKEI, and the DAX. Originality/relevance: The implications of these findings is that investors in the CAC 40 and NASDAQ should consider active volatility scaling because of multiple betas, and hence fundamental analysis is worth the time. This study adds to the literature on adaptive markets hypothesis as well as market efficiency and behavioural finance. Keywords: Adaptive markets; market efficiency; behavioural finance; financial markets; variance ratio